Omnichannel Strategy, Chatbot Responsiveness, and Same-Day Delivery's Influence on Customer Satisfaction in the Metaverse Commerce Era: A Case Study of Bukalapak and Zalora" - Nurfitriani; umi kulsum; Andrey Putra Susanto; Andi Indrawati (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This research aims to examine the influence of omnichannel strategy, chatbot responsiveness, and same-day delivery on customer satisfaction within the context of metaverse commerce. Using a quantitative approach with regression analysis, the study focuses on a case study of two e-commerce platforms, Bukalapak and Zalora. Data was collected through online questionnaires from a sample population of 300 people in Samarinda and its surrounding areas who have used these three services. The analysis method used was a combination of SEM-PLS.  The research findings show that all three independent variables—omnichannel strategy, chatbot responsiveness, and same-day delivery—have a significant influence on customer satisfaction. All alternative hypotheses were accepted. Among the three variables, same-day delivery showed the strongest influence, indicating that delivery speed is a crucial factor for customers. Meanwhile, chatbot responsiveness and omnichannel strategy also had a positive influence, although their impact was smaller compared to same-day delivery. The model was able to explain a large portion of the variation in customer satisfaction.  The implications of these findings suggest that companies like Bukalapak and Zalora need to prioritize delivery services to improve customer satisfaction. The results of this study can serve as a guide for optimizing omnichannel strategies, chatbots, and logistics. It is also recommended that future research includes additional variables and uses qualitative methods to provide a more comprehensive understanding.